Climate change impacts on precipitation and temperature in Prince Edward Island, Canada. Issue 1 (16th April 2021) - Bhatti, Ahmad Zeeshan; Farooque, Aitazaz Ahsan; Krouglicof, Nicholas; Peters, Wayne; Acharya, Bishnu; Li, Qing; Ahsan, M. Sheraz
Abstract: To understand climate change impacts on Prince Edward Island (PEI), Canada, historical daily precipitation and temperature of the island was investigated between the periods: 1931–60 (1940s), 1961–90 (1970s), and 1991–2020 (2000s) in its eastern, central, and western parts. Observed climatic data were utilized, augmented by some validated modeled data of Pacific Climate Impact Consortium (PCIC) for missing years. Statistically significant warming of the island was found ranging from 1.14°C in the east to 0.75°C in the west from the 1970s to 2000s. The warming trend during the period was distributed throughout the year including winters. In the east, mean monthly temperature significantly increased in all the months except for January, March, and June. Significant increase in temperature was found solely during August (+0.80°C) in central, and for August (+0.64°C), September (+0.99°C), and October (+0.73°C) in western parts. Proportionate increase in annual minimum temperature was greater than the maximum, particularly in eastern (+1.57°C) and central (+0.75°C) parts and thus indicated moderated cold there. Over the same 30‐year period, annual precipitation increased 6 percent in the east but decreased 5 and 8 percent in the central and the western PEI, respectively. The changes in precipitation were not statistically significant, except snowfall reduction (−20%) in the west, which was a statistically significant change. Interannual precipitation variations during wet and dry years having 20 and 80 percent probabilities of exceedance, respectively, ranged 350–470 mm/year during 1991–2020. Rainfall intensities, measured by hourly data, increased from 1.15 to 2.24 mm/hr, on average in central and western parts, respectively, in 2004–17 compared to 1970s. Impacts of the rising temperatures, decreasing precipitation, and uneven and intense rainfalls patterns on water resources and rainfed agriculture need further investigations. Climate change adaptations be included in existing water policies to mitigate the impacts. 摘要: 为研究气候变化对加拿大爱德华王子岛 (PEI) 产生的影响, 本文调查了1931‐1961年 (用1940s代替该时段) 、1961‐1990年(用1970s代替该时段)、以及1991‐2020(用2020s代替该时段)年间该岛东部、中部和西部的历史日均降水量及温度。使用了气候观察数据, 该数据通过由太平洋气候影响联盟 (Pacific Climate Impact Consortium) 证实的建模数据加以扩大, 弥补了无数据的年份。发现1970s‐2000s期间该岛出现统计学显著的变暖情况, 其中东部升高1.14°C, 西部升高0.75°C。该时段的变暖趋势是全年存在的, 包括冬季。东部地区每月平均温度显著增加, 1月、3月和6月除外。中部地区仅8月出现了显著温度上升 (0.80 °C), 西部地区8月、9月和10月出现了显著温度上升, 分别为0.64 °C、0.99 °C和0.73 °C。年度最低气温的成比例增长大于最高气温的增长, 尤其是在东部 (上升1.57 °C) 和中部 (上升0.75 °C), 因此寒冷气温有所减缓。在相同的30年里, 东部的年度降水量增加了6%, 而中部和西部分别下降了5%和8%。西部的降雪量显著减少了20%, 除此之外降水量变化并不显著。1991‐2020年间, 潮湿和干燥年份的年际降水量差异有20%和80%的概率存在降水过多的情况, 分别为每年350mm和470mm。与1970s相比, 2004‐2017年间中部和西部每小时降雨强度的平均增加量分别为1.15mm和2.24mm。温度上升、降水量减少、以及不均衡和剧烈降水模式对水资源及旱作农业产生的影响还需要进一步调查。现有水政策应包含气候变化适应措施, 以缓解该影响。 Resumen: Para comprender los impactos del cambio climático en la Isla del Príncipe Eduardo (PEI), Canadá, se investigaron las precipitaciones históricas diarias y la temperatura de la isla entre los períodos: 1931‐1960 (década de 1940), 1961‐1990 (década de 1970) y 1991‐2020 (década de 2000). en sus partes oriental, central y occidental. Se utilizaron los datos climáticos observados, aumentados por algunos datos modelados validados del Pacific Climate Impact Consortium (PCIC) para los años faltantes. Se encontró un calentamiento estadísticamente significativo de la isla entre 1, 14 C en el este y 0, 75 C en el oeste desde la década de 1970 hasta la de 2000. La tendencia al calentamiento durante el período se distribuyó a lo largo del año, incluidos los inviernos. En el este, la temperatura media mensual aumentó significativamente en todos los meses excepto enero, marzo y junio. Se encontró un aumento significativo de la temperatura únicamente durante agosto (+0, 80 ɑC) en el centro, y agosto (+0, 64 C), septiembre (+0, 99 C) y octubre (+0, 73 C) en la parte occidental. El aumento proporcional de la temperatura mínima anual fue mayor que la máxima, particularmente en las partes este (+1, 57 ɑC) y central (+0, 75 ɑC) y, por lo tanto, indicó un frío moderado allí. Durante el mismo período de treinta años, la precipitación anual aumentó un 6% en el este, pero disminuyó un 5% y un 8% en el PEI central y occidental, respectivamente. Los cambios en la precipitación no fueron estadísticamente significativos, excepto la reducción de nevadas (‐20%) en el oeste, que fue un cambio estadísticamente significativo. Las variaciones interanuales de las precipitaciones durante los años húmedos y secos, con probabilidades de superación del 20% y 80%, respectivamente, oscilaron entre 350 y 470 mm / año durante 1991‐2020. Las intensidades de las precipitaciones, medidas por datos horarios, aumentaron de 1, 15 a 2, 24 mm / h, en promedio en las partes central y occidental, respectivamente, en 2004‐17 en comparación con la década de 1970. Los impactos del aumento de las temperaturas, la disminución de las precipitaciones y los patrones desiguales e intensos de lluvias en los recursos hídricos y la agricultura de secano necesitan más investigaciones. Las adaptaciones al cambio climático se incluirán en las políticas de agua existentes para mitigar los impactos.